Distinct microbiome composition and metabolome exists across subgroups of elite Irish athletes - O'Donovan, C. M.; Madigan, S. M.; Garcia-Perez, I.; Rankin, A.; O'Sullivan, O. O.; Cotter, P. D. (Journal of Science and Medicine in Sport, 2020)
Objectives: The gut microbiome has begun to be characterised in athlete groups, albeit, to date, only across a subset of sports. This study aimed to determine if the gut microbiome and metabolome differed across sports classification groups (SCGs) among elite Irish athletes, many of whom were participating in the 2016 Summer Olympics. Methods: Faecal and urine samples were collected from 37 international level athletes. Faecal samples were prepared for shotgun metagenomic sequencing and faecal and urine samples underwent metabolomic profiling. Results: Differences were observed in the composition and functional capacity of the gut microbiome of athletes across SCGs. The microbiomes of athletes participating in sports with a high dynamic component were the most distinct compositionally (greater differences in proportions of species), while those of athletes participating in sports with high dynamic and static components were the most functionally distinct (greater differences in functional potential). Additionally, both microbial (faecal) and human (urine) derived metabolites were found to vary between SCGs. In particular cis-aconitate, succinic acid and lactate, in urine samples, and creatinine, in faeces, were found to be significantly different between groups. These differences were evident despite the absence of significant differences in diet, as determined using food frequency questionnaires, which were translated into nutrient intake values using FETA. Conclusions: Differences in the gut microbiome and metabolome between groups, in the absence of dietary changes, indicates a role for training load or type as a contributory factor. Further exploration of this hypothesis has the potential to benefit athletes, aspiring athletes and the general public.